Mechanisms of Hypercapnia-Induced Endoplasmic Reticulum Dysfunction - Kryvenko, Vitalii; Vadász, István (Frontiers in Physiology, 2021)
Protein transcription, translation, and folding occur continuously in every living cell and are essential for physiological functions. About one-third of all proteins of the cellular proteome interacts with the endoplasmic reticulum (ER). The ER is a large, dynamic cellular organelle that orchestrates synthesis, folding, and structural maturation of proteins, regulation of lipid metabolism and additionally functions as a calcium store. Recent evidence suggests that both acute and chronic hypercapnia (elevated levels of CO2) impair ER function by different mechanisms, leading to adaptive and maladaptive regulation of protein folding and maturation. In order to cope with ER stress, cells activate unfolded protein response (UPR) pathways. Initially, during the adaptive phase of ER stress, the UPR mainly functions to restore ER protein-folding homeostasis by decreasing protein synthesis and translation and by activation of ER-associated protein degradation (ERAD) and autophagy. However, if the initial UPR attempts for alleviating ER stress fail, a maladaptive response is triggered. In this review, we discuss the distinct mechanisms by which elevated CO2 levels affect these molecular pathways in the setting of acute and chronic pulmonary diseases associated with hypercapnia.